Techniques for in vitro conservation and their use for establishing germplasm banks of tropical crops. - Sánchez-Chiang, Neiva; Jiménez, Víctor M. (Agronomía Mesoamericana, 2010)
The aim of this literature review is to describe the main techniques for short and long term germplasm conservation. These techniques allow establishment of germplasm banks. This article focuses on their use in tropical crops. In vitro preservation techniques have allowed conservation of plant genetic resources for further use in plant breeding, research and food security purposes. Several research centers have used these techniques for tissue and seed storage of tropical crops, mainly for those that are difficult to preserve conventionally.